Towards principled learner selection - Rattray, Andrew (2013)
Long learner evaluation times are no longer exceptional and often there is insufficient time to exhaustively test all candidate options. When deciding which learners to use, practitioners must rely on ad hoc testing and luck to identify the most accurate one. Given the importance of classification in decision making, this is unsatisfactory. Progress towards a principled approach requires accurate predictions of learner accuracy and evaluation time and this study examines the potential of traditional meta-learning approaches, with their emphasis on indirect explanatory variables, to deliver the required solutions.